Characterization of Au Thin Films With Laser Annealing at Different Energies on P-Type Silicon for Flat Panel Display Application - Md Khairi, Nur Syamimi; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2024)
In TFTs, the metal-semiconductor contact links the semiconductor structure to external influences impacting flat panel display functionality. However, due to the inherent amorphous nature of the materials, achieving lower contact resistance and enhanced conductivity are challenging in thin metal contacts. This research involved depositing Au thin film layer by DC sputtering technique onto p-type silicon subsequently annealed using Nd:YAG pulsed laser at different energy levels. The topology, chemical, electrical and optical properties of treated Au thin film were examined via Atomic Force Microscopic (AFM), Energy Dispersive X-ray spectroscopy (EDX), Four Point Probe (4PP), and Ultraviolet-Visible Spectroscopy (UV-VIS), respectively. Results indicated that the 170 mJ annealed sample shows the highest surface roughness compared to the as-deposited sample, impacting the enhancement of conductivity of Au thin film. The sample exhibited relatively low absorbance levels below 22%, attributed to its high reflectivity. Overall, all Au thin films treated with Nd: YAG laser showed substantial improvement, primarily due to enhancements in their structural properties.